2010
DOI: 10.1146/annurev.resource.012809.103919
|View full text |Cite
|
Sign up to set email alerts
|

Providing Safe Water: Evidence from Randomized Evaluations

Abstract: This paper uses a public economics framework to review evidence from randomized trials on domestic water access and quality in developing countries and to assess the case for subsidies. Water treatment can cost-effectively reduce reported diarrhea. However, many consumers have low willingness to pay for cleaner water; few households purchase household water treatment under retail models. Free point-of-collection water treatment systems designed to make water treatment convenient and salient can generate take-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 46 publications
3
69
0
Order By: Relevance
“…Our WTP estimates indicate that reaching 50% of the target population would require subsidies of up to 89% of retail for the pot filter with its container; the median bid in these low-income communities was 11% of the retail price. These low WTP figures have also been reported in previous research (Ahuja et al, 2010;Amrose et al, 2015) with revealed WTP studies almost always yielding lower numbers than stated WTP (Luoto et al, 2012;Ahuja et al, 2010;Kremer et al, 2009;Orgill et al, 2013). The development of less expensive alternatives is promising, however; we found that a generic disinfectant-coagulant would be as acceptable to consumers as PuR, indicating a potential market for a generic version of this type of HWTS technology.…”
Section: Conclusion and Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our WTP estimates indicate that reaching 50% of the target population would require subsidies of up to 89% of retail for the pot filter with its container; the median bid in these low-income communities was 11% of the retail price. These low WTP figures have also been reported in previous research (Ahuja et al, 2010;Amrose et al, 2015) with revealed WTP studies almost always yielding lower numbers than stated WTP (Luoto et al, 2012;Ahuja et al, 2010;Kremer et al, 2009;Orgill et al, 2013). The development of less expensive alternatives is promising, however; we found that a generic disinfectant-coagulant would be as acceptable to consumers as PuR, indicating a potential market for a generic version of this type of HWTS technology.…”
Section: Conclusion and Discussionsupporting
confidence: 80%
“…The estimation and appropriate targeting of subsidies is a contested topic in the development literature, but many researchers have argued that, without subsidies, universal access to safe drinking water will not be possible (Ahuja et al, 2010;Amrose et al, 2015). We conclude that, for a low-income country looking to improve the health of its citizens through scaling up HWTS, there may be no "low-cost" options to safe drinking water for all.…”
Section: Conclusion and Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…21 Dilute chlorine, branded as WaterGuard, was widely promoted and distributed by the manufacturer in Kenya (Population Services International, Washington, DC), and therefore, it was familiar to the study population and could be considered an intervention that had already been scaled up. Turbidity is not a major concern in this part of Kenya, where most people rely on groundwater or rainwater for drinking; thus, filters were not seen to have a significant advantage over chlorine.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, demand-side factors that impede coverage may arise through lack of knowledge or understanding of the benefits provided by different services. In these cases, informational campaigns can have a significant role in increasing the take-up of essential services (Ahuja, Kremer, & Zwane, 2010).…”
Section: Discussionmentioning
confidence: 99%